At the origins of the social and literary movement of the early XIX century: The Friendly Literary Society - Lyovin, Sergey Vladimirovich (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2025)
The first quarter of the XIX century is the period of the emergence of various literary salons which had a great influence on the spiritual life of Russian society. Famous poets, prose writers, translators and journalists honed their skills there. The paper considers the Friendly Literary Society which formed in Moscow in January 1801. The author comes to the conclusion that it can be considered a prototype of future literary salons. The Society did not outgrow the framework of a friendly circle, but the issues discussed by its participants did not lose their relevance in subsequent decades.